The Impact of Gadget Usage Intensity on Language and Speech Development in Preschool Children in Denpasar City - Dewi, Ni Made Ovilianty Chandra; Winaya, I Made Niko; Kinandana, Gede Parta; Sundari, Luh Putu Ratna (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction: The rapid advancement of technology, including the widespread use of gadgets across various age groups, affects even preschool children. Excessive gadget use can reduce opportunities for children to learn and receive stimulation from their environment. Stimulation may help the development of language and speech skills in children. Language and speech development delays can subsequently impact a child's overall development. Methods: This study employed an observational analytic method with a cross-sectional approach. Subjects were selected using purposive sampling. The intensity of gadget usage was measured through questionnaires filled out by the subjects' parents, while language and speech development were assessed using the Denver II test. Results: The study included 108 subjects. Non-parametric Spearman's rho analysis revealed a p-value of 0.000 (p < 0.05) and a correlation coefficient (r) of 0.394. Conclusion: The results of this study indicate a relationship between the intensity of gadget usage and the language and speech development of preschool children in Denpasar City. Keywords: intensity, gadgets, language, speech, children